Examination Of The Ability Of Boys in The Last Childhood To Say No According To Their Participation in Recreational Activities - Furkan Minver; Ezgi Ertüzün; Özlem Yalçın (Türk Spor ve Egzersiz Dergisi)
Being able to say no is a very important coping skill for the last childhood period, as it is for every period of life. Participating in recreational activities improves children's ability to say no and increases their sense of curiosity. In this study, the ability of saying no to children who participated in recreational football activities in their last childhood and those who did not participate in any recreational activity was compared. The study group of the research consists of 211 boys in the last childhood period, 105 of whom participated in recreational activities between the ages of 9-11 in Ankara and 106 of whom did not participate in any recreational activities. In the study, Yılmaz and Sözer's (2018) Ability to Say No Scale and Personal Information Form were used. Descriptive statistics were used in the analysis of the data. There was no significant difference between children who participated in recreational fuubol activities and those who did not. In further analysis, it was determined that the children of university graduate fathers had higher ability to say no than the children of high school graduate fathers.